Effectiveness Of A Modern Teba-Based Educational Communication Strategy In Improving Awareness Of Independent Waste Management - Mohammad Mulyadi Prasetyo; Andi Taskirah; Andi Andariana (Indonesian Journal of Educational Technology, 2026)
This study examined the effectiveness of a Modern TEBA-based educational communication strategy in strengthening participants' awareness of independent waste management in RT 01/RW 03, Paccerakkang Urban Village. A quantitative approach with a pre-experimental one-group pretest-posttest design was applied. The participants were 50 residents who joined an environmental education activity on May 29, 2026. The intervention combined interactive outreach, guided discussion, technical demonstration, hands-on construction of two Modern TEBA units, and a household organic waste sorting simulation. Data were collected from pretest and posttest scores on a 0-100 scale and supported by observations of the learning process. The mean pretest score was 30.30, while the mean posttest score increased to 68.30, producing an average gain of 38.00 points. The mean normalized gain was 0.53, which indicated moderate improvement. The Shapiro-Wilk test on gain scores showed a non-normal distribution (p = 0.001); therefore, the Wilcoxon signed-rank test was used. The test confirmed a significant difference between pretest and posttest scores (W = 0.00, p < 0.001). These findings show that a practice-oriented educational communication strategy can improve participants' initial knowledge and awareness of independent waste management. With continuous mentoring, the program can be adapted as a non-formal environmental education model at the urban village level.